Beyond (Human) Rights? - Armstrong, Philip (Disability Studies Quarterly, 2009)
The essay responds to the pervasive appeals to rights discourse during the 2007 Nairobi workshop on "Disability, Culture, and Human Rights." Taking its point of departure from Wendy Brown's rethinking of rights discourse in States of Injury, as well as from a range of recent texts that seek to reopen the presuppositions informing the role of rights in relation to concepts of state sovereignty and contemporary globalization, the essay seeks to outline a number of questions and problems concerning rights in contexts of disability. In addressing the conflicts and paradoxes opened up between rights as human and universal and rights as geopolitically circumscribed and historically contingent, the essay argues that it is these same conflicts and paradoxes that shape and even over-determine the workshop’s initiative to reconfigure the 2003 Disability Act in Kenya.